An Innovative Application of Super-Paramagnetic Iron Oxide Nanoparticles for Magnetic Separation - G. Banis; M.E. Kouli; A. Ferraro; A. Molino; D. Karatza; S. Chianese; D. Musmarra; E. Hristoforou (Chemical Engineering Transactions, 2017)
In the last decades, iron oxide nanoparticle application has taken root in several technological fields, such as magnetic separation of biomolecules, biosensors, bio-fuel production, nano-devices and nano-adsorption. Various approaches can be found for the magnetic nanoparticle manufacturing. Among them a new technology to manufacture core-cell super-paramagnetic iron oxide nanoparticles (SPIONs), based on a vapour composition using single ion precursors, like cyclodextrines, has been recently developed.